(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Foetal death remains a significant and understudied problem. Foetal autopsy and placental examination offer much valuable information for the formulation of the cause of death. The present study was undertaken with an aim to provide data regarding the cause and circumstances of foetal death and to provide autopsy findings in these deaths. The retrospective study was carried out from 2004 through to 2008. All cases listed as foetal death or stillbirths were included. The male: female ratio was 1:1.2 and their age ranged from 16 weeks to full term. Most foetuses (n = 26, 76.47%) were older than 28 weeks. The majority (n = 25, 73.52%) were externally normal, apart from decomposition and maceration, and only 2 (5.88%) had exhibited gross congenital anomaly. Considering the manner of death, 70.58% were natural, 14.70% homicidal and 14.70% were undetermined cases.